Bolts, hexagon head, relieved shank, long thread, in heat resisting nickel base alloy NI-P101HT (Waspaloy), silver plated. Classification:1210 MPa (at ambient temperature)/730 °C. (15th July 1998) - British Standards Institution,
No abstract available